Young Consumers’ Intention to use Blu by BCA: An Extended TAM - Widhi Ariyo Bimo; Hanif Zaidan Sinaga; Mohammad Jibriel Avessina; Ali Nurjali; Nurwinda Nurwinda (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study examines factors influencing intention to use the blu by BCA digital banking application among young consumers in Bogor, Indonesia. An extended Technology Acceptance Model was tested by incorporating perceived usefulness, perceived ease of use, perceived risk, trust, and convenience. Data were collected through a cross-sectional online survey of 100 blu by BCA users selected using purposive sampling and analyzed using item-validity testing, Cronbach's alpha, and multiple linear regression. All reported predictor items met the stated validity and reliability criteria. Convenience had a significant positive effect on intention to use (B = 0.432; p = 0.001). Trust (B = 0.229; p = 0.051) and perceived ease of use (B = 0.485; p = 0.088) were positive but not significant at the 5% level. Perceived risk was negative but non-significant (B = -0.183; p = 0.489), while perceived usefulness was negligible (B = -0.006; p = 0.959). The findings indicate that practical accessibility and transaction efficiency receive the strongest empirical support in the reported model. Digital banks should prioritize frictionless transactions, reliable access, and transparent security communication while strengthening distinctive service value.